Phenomena of fluorescence and phosphorescence - Baghel, R N; Luka, A K (Recent Research in Science and Technology, 2012)
The present paper introduces the basic concepts of luminescence via defining, classifying and enumerating the applications of various types of luminescence. Two key aspects of luminescence- fluorescence and phosphorescence - have been dealt with theoretically for monomolecular and bimolecular materials. The rate equations of these materials have been derived and discussed. The rise and decay of luminescence intensities for both monomolecular and bimolecular materials have been discussed.